2004
DOI: 10.1159/000075337
|View full text |Cite
|
Sign up to set email alerts
|

Association between Major Depressive Disorder and the –1438A/G Polymorphism of the Serotonin 2A Receptor Gene

Abstract: This study investigated the possible effect of the –1438A/G single-nucleotide polymorphism in the promoter region of the serotonin 2A receptor (5-HTR2A) gene on major depressive disorder (MDD) in a Korean population. This polymorphism was analyzed in 189 patients with MDD and in 148 unrelated healthy controls using a case-control design, which revealed a significant difference in the genotype distributions (χ2 = 10.78, d.f. = 2, p = 0.005). The frequency of the –1438G allele was also much higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 19 publications
4
39
0
2
Order By: Relevance
“…Regarding association studies in various ethnic samples, the rs6311 A allele has been found to be associated with an increased risk for MDD in Swedish (Jansson et al, 2003) and Danish (Christiansen et al, 2007) populations, whereas the association between the rs6311 G allele and an increased risk for MDD has been reported in a Korean study (Choi et al, 2004). Nevertheless, negative associations between this SNP and MDD have been revealed in other populations including the Japanese (Ohara et al, 1998;Kishi et al, 2009), Israeli-Jewish (Frisch et al, 1999), Caucasians from France (Bonnier et al, 2002), and Finnish (Illi et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Regarding association studies in various ethnic samples, the rs6311 A allele has been found to be associated with an increased risk for MDD in Swedish (Jansson et al, 2003) and Danish (Christiansen et al, 2007) populations, whereas the association between the rs6311 G allele and an increased risk for MDD has been reported in a Korean study (Choi et al, 2004). Nevertheless, negative associations between this SNP and MDD have been revealed in other populations including the Japanese (Ohara et al, 1998;Kishi et al, 2009), Israeli-Jewish (Frisch et al, 1999), Caucasians from France (Bonnier et al, 2002), and Finnish (Illi et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…5-HT2A receptor polymorphisms are generally not associated with major depression (Zhang et al 1997;Frisch et al 1999;Tsai et al 1999;Minov et al 2001;Oswald et al 2003;Choi et al 2004;Khait et al 2005;Levinson 2005). …”
Section: -Ht Receptorsmentioning
confidence: 99%
“…Recent evidence supports this hypothesis. The serotonin 2A gene was associated with MDD in the Korean population, 22 but not in Japanese population. 23 rs6295 (C-1019G) in the promoter region regulates HTR1A transcription.…”
Section: Discussionmentioning
confidence: 83%